A New Scheme for Considering Soil Water‐Heat Transport Coupling Based on Community Land Model: Model Description and Preliminary Validation. (2nd April 2018) - Wang, Chenghai; Yang, Kai
Abstract: Land surface models (LSMs) have developed significantly over the past few decades, with the result that most LSMs can generally reproduce the characteristics of the land surface. However, LSMs fail to reproduce some details of soil water and heat transport during seasonal transition periods because they neglect the effects of interactions between water movement and heat transfer in the soil. Such effects are critical for a complete understanding of water‐heat transport within a soil thermohydraulic regime. In this study, a fully coupled water‐heat transport scheme (FCS) is incorporated into the Community Land Model (version 4.5) to replaces its original isothermal scheme, which is more complete in theory. Observational data from five sites are used to validate the performance of the FCS. The simulation results at both single‐point and global scale show that the FCS improved the simulation of soil moisture and temperature. FCS better reproduced the characteristics of drier and colder surface layers in arid regions by considering the diffusion of soil water vapor, which is a nonnegligible process in soil, especially for soil surface layers, while its effects in cold regions are generally inverse. It also accounted for the sensible heat fluxes caused by liquid water flow, which can contribute to heat transfer in both surface and deep layers. The FCS affects the estimation of surface sensible heat (SH) and latent heat (LH) and provides the details of soil heat and water transportation, which benefits to understand the inner physical process of soil water‐heat migration. Key Points: A fully coupled water‐heat transport scheme was incorporated into CLM4.5 for studying the detail of soil water and heat transport FCS generally improved the simulation of soil moisture and temperature especially in arid regions Soil water vapor diffusion has considerable effects on the water‐heat transport in surface layers and surface diabatic heating